Concentration and Time Exposure Determination of Methanol Extract from Carica papaya Leaves in The Larvicidal Activity Against Aedes aegypti Larvae - Sudarwati, Tri Puji Lestari; M. A Hanny Ferry Fernanda (Journal of Research and Technology, 2021)
Dengue Haemorrhagic Fever (DHF) is a disease caused by dengue virus which is transmitted through Aedes aegypti mosquito bite. Efforts to control the widespread of the vectors have been made using biological agents and also chemical compound. Chemicals known as a standard protocol have raised concerns about resistance and harmfulness to the environment. Hence, the present study was aimed to explore the larvicidal activity of papaya (Carica papaya) leaf extract against Aedes aegypti larvae in regards to the optimum concentration and time exposure.  Preparation the obtained extract was diluted to make a serial concentration. These solutions were made by pipetting 0.65 mL, 1.25 mL, 2.5 mL, 5.0 mL, and 10.0 mL of extract into 10.0 mL volumetric flasks and dilute with distilled water. The test solution was poured into a glass jar contained 90 mL of distilled water and filled with 20 third instar larvae. Each experiment was replicated four times. The larval mortality was recorded in 24h and calculated as a percentage of total larvae used in the experiment. The table above shows the value of LC50 And LT50 from toxicity assay of papaya leaf extract. According to the LT50 value, it can be seen that the lowest LT50 of 1,006h occurred at the concentration of 11000 ppm. Moreover, calculated LC50 is 4929,344 ppm. Based on these results, papaya leaves have the ability to Aedes aegypti larvaside so that it can help in breaking the chain of development of Aedes aegypti.